Evaluación de los niveles de calidad de los servicios turísticos de Tamshiyacu al año 2024 - Davila Nascimento, Mariathais Aleli (2024)
The quality of tourism services currently provided by the city of Tamshiyacu in the Fernando Lores district demonstrates the possibilities of tourism that could be a source of employment due to the ecological diversity that it shows in its locality. Currently, the directorate of foreign trade, tourism and crafts of the Loreto region, created measures, plans and investment projects that seek to better position the capital cities of the districts and provinces of Loreto in the medium and long term. Given these circumstances, it is necessary to determine the level of quality of tourism services in the capital of the Fernando Lores district, taking as reference the requirements that SUPREME DECREE No. 001-2015-MINCETUR and MINISTERIAL RESOLUTION No. 150-2015- PCM The research is proposed through the description and formulation of the general problems of tourism agents such as the conditions of accommodation, catering, transportation and tourist orientation, the objectives, the hypothesis with their respective variables, indicators and indices that will give us a clear vision for the analysis. The research design is proposed through a non-experimental, descriptive transactional design, which will allow us to propose the hypothesis with its variables and indicators for an analysis that will determine the conclusions and recommendations.